Determinants of COVID-19 Vaccine Acceptance and Hesitancy: A Health Care Student-Based Online Survey in Northwest China - Zhang, Juxia; Dean, Judith; Yin, Yuhuan; Wang, Dongping; Sun, Yanqing; Zhao, Zhenhua; Wang, Jiancheng (Frontiers in Public Health, 2022)
Background: With the spread of COVID-19 around the world, herd immunity through vaccination became a key measure to control the pandemic, but high uptake of vaccine is not guaranteed. Moreover, the actual acceptance of COVID-19 vaccination and associated factors remain uncertain among health care students in Northwest of China. Methods: A cross-sectional survey of a sample of 631 health care students was performed using a questionnaire developed through Wen Juan Xing survey platform to collect information regarding their attitudes, beliefs and acceptance of COVID-19 vaccination. Binary logistic regression analyses were performed to identify the association between vaccination willingness and demographics, attitudes and beliefs in order to find out factors actually effect acceptance and hesitancy of COVID-19 vaccine among healthcare students. Results: Overall, 491 (77.81%) students actually received the COVID-19 vaccine, of the 140 unvaccinated, 69 were hesitant and 71 rejected. Binary logistic regression analysis showed that the actually vaccinated individuals were those who mostly believed the effectiveness of COVID-19 vaccine (OR=2.94, 95%CI: 1.37, 6.29), those who mostly felt it is their responsibility to receive the vaccine to protect others from infection (OR=2.75, 95%CI: 1.45, 5.23), with less previous experience about other vaccines (OR=1.70, 95%CI: 1.06, 2.72), students who mostly thought COVID-19 be very severe (OR=1.77, 95%CI: 1.07, 2.93), and students who mostly thought COVID-19 vaccine as one of the best protection measures (OR=1.68, 95%CI: 1.03, 2.76). Concerns about side effects of vaccines (OR=0.30, 95%CI: 0.18, 0.51), and the use of personal protective behavior as an alternative to COVID-19 vaccination (OR=0.16, 95%CI: 0.06, 0.39) hindered the vaccine acceptance. Conclusions: Our study showed higher COVID-19 vaccine acceptance among healthcare students. However, the individuals with vaccine hesitancy and rejection were still worrying. Vaccine safety and effectiveness issues continue to be a major factor affecting students acceptance. To expand vaccine coverage in response to the COVID-19 pandemic, appropriate vaccination strategies and immunization programs are essential, especially for those with negative attitudes and beliefs.